2018
DOI: 10.4078/jrd.2018.25.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Involvement of Juvenile Temporal Arteritis Associated with Kimura Disease

Abstract: Juvenile temporal arteritis (JTA) is a localized nodular arteritis confined to the temporal artery without evidence of systemic inflammation, and it occurs mainly in patients younger than 50 years. From the first case report, the pathological features of JTA have been suspected to be the morphological equivalent of Kimura disease (KD), which has been supported further by the concurrent cases of JTA with KD. We present the first case of bilateral JTA accompanying KD, which was confirmed by histological and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…These patients complained of painless nodules on their temple, and the pathologic findings revealed nongiant cell inflammation of temporal arteries [4]. From then on until February 2019, according to our literature review through PubMed and Scopus, 18 more cases have been reported [23567891011121314151617181920]. Including the present case, a total of 23 cases of JTA were reported and their mean age was 27 years (range, 7 to 44 years) and there was the male predominance (18 men and 5 women).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients complained of painless nodules on their temple, and the pathologic findings revealed nongiant cell inflammation of temporal arteries [4]. From then on until February 2019, according to our literature review through PubMed and Scopus, 18 more cases have been reported [23567891011121314151617181920]. Including the present case, a total of 23 cases of JTA were reported and their mean age was 27 years (range, 7 to 44 years) and there was the male predominance (18 men and 5 women).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the 18 cases that resolved after excision recurred later on the opposite side [1218]. Of the 3 cases without excision, 2 were treated with steroid because of combined disease such as Kimura disease [20] or HES [12], and 1 was treated with tocopherol nicotinate [8], and these patients reported no recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation